The Influence of Visual Recognition and Preference in Serious Game Development: A Mixed-Method Study in Nepal - Hua Bai; Dayana Shakya; Ulf Wilhelmsson; Jon Victor Bankler; Ran Zhang; Anna-Sofia Alklind Taylor; Abhinav Vaidya; Natalia Oli; Alexandra Krettek; Mikael Lebram (International Journal of Serious Games)
Understanding players’ diverse visual recognition and preferences, especially in cross-cultural contexts, is critical for the creation of effective serious games. This study aimed to examine how varying levels of fidelity affect players' visual recognition, preference, and overall experience in serious gaming, using a mixed-method case study in the Bhaktapur district, Kathmandu, Nepal. Forty-four participants, aged 13 to 16 years, were enrolled in an A/B gameplay test. Fourteen students participated in in-depth interviews, thirty-six completed a questionnaire, and twenty-two provided valid telemetry data. We found that higher fidelity led to more positive affect, higher familiarity, better recognition, stronger preference, and positive emotional response from players. However, challenges were encountered regarding the identification of local food items. This highlights the key role of visual literacy, as adolescents are more influenced by familiar media than by real-life experiences. Effective visual communication in serious games should consider individual differences and the playing environment.